IMPLEMENTASI FRAMWORK BOOSTRAP PADA WEBSITE STMIK PRABUMULIH - Ahmat Josi (Jurnal Mantik Penusa, 2016)
Increased technological needs encourage people to develop new technologies for data processing and information can be done easily and quickly. One of that technology is growing repidly this time a technology information, internet technology. With the internet technology will be make it esier and fast to search information, one of resource which can be used as a reference is the website. Website or site can be inpreted like page set to display text information data, slow image data or moving image data, animation data, voice, video and combination of all that is static and dynamic, and combined form a series of buildings have interrelated whe each linked to the network pages, website utilization many many use by the company, government agencies, schools and colleges, one of them is STMIK Prabumulih college. This time STMIK Prabumulih has had website but the website STMIK Prabumulih not yet Responsive so when accessed through various flatform page of views of the website can’t adjust with the flatform, therefore website visitors will be a little trouble because view the website monotonous.